ANALISIS EFEKTIVITAS PENUKAR KALOR PIPA HELIKAL DESTILASI MINYAK ATSIRI KAYU PUTIH - Antonius Hatumessen; Nicolas Titahelu; Cendy S. Tupamahu (ALE Proceeding, 2021)
The Eucalyptus plant is one of the essential oil-producing plants. Eucalyptus oil processing generally uses the distillation method. Traditionally used eucalyptus oil distillation uses a straight pipe condenser. The weakness of the straight pipe condenser is that the temperature of the condensate that comes out is still very high, this shows that the effectiveness of the straight pipe condenser is not optimal. To optimize the effectiveness of the distillation system condenser, a condenser with a helical pipe type condenser is designed in the essential oil distillation system. This study will vary the ratio of the pitch distance to the diameter of the condenser pipe, which aims to obtain an effective helical coil pitch ratio to optimize the effectiveness of the helical pipe condenser. This study uses the simulation method on COMSOL Multiphysics 5.4. The pitch ratio variant used is 2.1; 2.62; 3.15; 3.67; 4.2. The parameters that are constant in this study are the inlet fluid temperature on the tube side 373 K, the inlet fluid temperature on the shell side 288 K, the fluid inlet velocity on the tube side 0.2 m/s, and the fluid inlet velocity on the shell side 1 m/s. The results of the simulation by varying the pitch ratio show that the effectiveness increases as the pitch ratio value decreases, where the highest effectiveness is shown at pitch ratio of 2.1 which 75.9% and the lowest effectiveness is shown to pitch ratio of 4.2 which 70.7%.